2007
DOI: 10.1093/ecam/nem084
|View full text |Cite
|
Sign up to set email alerts
|

A Review of CAM for Procedural Pain in Infancy: Part I. Sucrose and Non‐Nutritive Sucking

Abstract: There is increasing concern regarding the number of painful medical procedures that infants must undergo and the potential risks of alleviating infant pain with conventional pharmacologic agents. This article is Part I of a two-part series that aims to provide an overview of the literature on complementary and alternative (CAM) approaches for pain and distress related to medical procedures among infants up to six weeks of age. The focus of this article is a review of the empirical literature on sucrose with or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 56 publications
(77 reference statements)
0
22
0
7
Order By: Relevance
“…All sweet solutions are administered in the same way, on the infants' lateral side of the tongue prior to or 2 min before the procedure through a syringe slowly over 30 s [9,18]. Another administration technique is through the use of non-nutritive sucking using paciier to improve its efectiveness [11,19].…”
Section: Sweet Solutions In the Clinical Setings And Guidelinesmentioning
confidence: 99%
See 2 more Smart Citations
“…All sweet solutions are administered in the same way, on the infants' lateral side of the tongue prior to or 2 min before the procedure through a syringe slowly over 30 s [9,18]. Another administration technique is through the use of non-nutritive sucking using paciier to improve its efectiveness [11,19].…”
Section: Sweet Solutions In the Clinical Setings And Guidelinesmentioning
confidence: 99%
“…Although there is no evidence yet about the dose-response efects [21], dose ranging from 0.5 to 2 mL of 12-24% strength show pain-relief efect [11,22]. For premature neonates, dose is calculated in accordance to their weight/volume ratio.…”
Section: Sweet Solutions In the Clinical Setings And Guidelinesmentioning
confidence: 99%
See 1 more Smart Citation
“…1,61,63 The same argument applies to glucose, because many studies have shown that glucose, if sufficiently concentrated, also reduces pain in infants. 1,78,79 However, although basic science and clinical researchers and clinicians continue to address the knowledge and research gaps relating to analgesic effects and mechanisms of sucrose, we need to remain cognizant that untreated or poorly treated pain in fragile infants has well-documented short-term adverse consequences and potential longer-term negative effects. 4 Clinicians therefore have an ethical responsibility to minimize pain exposure; use sucrose appropriately for single painful procedures, along with other evidence-based strategies including NNS, kangaroo care, and breastfeeding when feasible; 80 and monitor use and effectiveness of these strategies over short-and long-term periods.…”
Section: Practice and Research Implicationsmentioning
confidence: 99%
“…There have been several reviews describing the literature in support of oral sucrose and non-nutritive sucking for procedural pain in infants. [59][60][61] A small amount (between 0.05 and 0.5 mL) of a 24% sucrose solution is provided orally to the infant. Two minutes prior to the beginning of the procedure, the sucrose is placed either directly on the infant's tongue or on a pacifier that is placed in the infant's mouth.…”
Section: Pharmacological and Physical Interventionsmentioning
confidence: 99%